HASIL BELAJAR KOGNITIF SISWA MELALUI PENERAPAN TEKNIK SELF ASSESSMENT PADA MATERI IMPULS DAN MOMENTUM DI SMAN 2 TAMBANG - Niarsih, Syafrida; Azizahwati, Azizahwati; Rahmad, Muhamad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the cognitive learning outcomes of students through the application of self assessment technique on impuls and momentum. The research method used was Pre-Experimental design with the design of Intact Group Comparison. The research subjects were students of X class SMAN 2 tambang, in which devided into the experimental class and the control class. The experimental class uses a self assessment technique learning model and a control class with a conventional learning. The data was obtained from cognitive learning outcomes test which given to students after the learning process was carried out. Data were analyzed descriptively to provide an overview of students cognitive learning outcomes including students absorption and learning effectiveness on indication of impuls and momentum material. The research result obtained were the average of students absorption ability in the experimental class was 75,43% and 69,71% for control class. Thus it can be concluded that the implementation of self assessment technique was effective to increase student cognitive learning outcomes on impuls and momentum material in class X SMAN 2 Tambang.Key Words: Self Assessment Technique, Cognitive Learning Outcomes, Impuls And Momentum